Penggabungan Gaya Ekspositori dan Observasional dalam Produksi Film Dokumenter - Iwan Koswara; Jimi Narotama Mahameruaji; Marsha Diva Fidela Saputra (Comit: Communication, Information and Technology Journal, 2024)
Documentary films have evolved significantly and have a character based on their complex and profound narratives that present facts based on data. This research aims to explore the impact of the integration of documentary style between expository and observational on the role of scriptwriters in documentary production. This is based on the increasing production of documentary films in Indonesia across various channels on platforms like YouTube, one of which is Channel Watchdoc. Using a descriptive approach, data were collected through theories, perspectives, and the personal experiences of the researcher as a scriptwriter in documentary production. The results indicate that scriptwriters play a crucial role in creating the story and maintaining the narrative flow to appear natural and spontaneous. Additionally, scriptwriters ensure the consistency of the pre-planned focus, even with significant improvisations based on field occurrences. The conclusion of this research emphasizes that, despite the various challenges posed by combining expository and observational storytelling techniques, the presence of skilled scriptwriters is essential for maintaining the naturalness and consistency of a documentary film. This approach offers a new perspective for viewers, allowing them to directly perceive situations and conditions with the hope of providing benefits and inspiring action and change.